Global Mountain Safeguard Research (GLOMOS): Five Years Into Action - Stefan Schneiderbauer; Paola Fontanella Pisa; Lina Rodriguez; Navneet Kumar; Federica Romagnoli; Dipesh Chapagain; Jörg Szarzynski (Mountain Research and Development)
Global Mountain Safeguard Research (GLOMOS), a joint scientific program between the United Nations University (UNU) Institute for Environment and Human Security, Bonn, Germany, and Eurac Research, Bolzano, Italy, has concluded the first 5 years of its research in action. GLOMOS represents the only mountain-focused research program within the global system of the UNU. With a focus on risks in mountains, and considering the complex interrelations and interdependences of upland and lowland areas, GLOMOS fosters the development of sustainable and resilient mountain communities. The GLOMOS principle is to involve relevant stakeholders and local actors in its work from the beginning of the design phase of projects, recognizing the integration of Indigenous and local knowledge systems as a foundation for risk reduction and the enhancement of climate change adaptation. This article summarizes GLOMOS's scientific foci and approaches, which have recently been revised and updated based on experience gained from the initial phase. Selected results from the first 5-year phase of the program are also presented. Finally, GLOMOS invites interested scientific initiatives and research entities to cooperate with the program to jointly conduct cutting-edge research and bridge science, policy, and practice for safe and sustainable mountain livelihoods worldwide.